"Half the Truth is Often a Great Lie": Deep Fakes, Open Source Information, and International Criminal Law. (2019) - Koenig, Alexa
Abstract : The video opens with a man—now known to be Commander Al-Werfalli of the elite Libyan Special Forces team al Saiqa—throwing a quick glance over his shoulder as a black SUV rolls off camera. Cradling a gun, he saunters towards three men kneeling on a sidewalk, hands bound behind their backs, faces turned toward the wall. He raises the gun in his left hand. Without pausing, he walks methodically down the row, a bullet punctuating every other step. The men slump forward as they fall. Werfalli's first hint of emotion is visible only when he unloads multiple bullets into the final body.